Thought
1 online resource (x, 326 pages).
Keywords: "Of all the topics in the history of philosophy the history of different forms of thinking and contemplation is one of the most important, and yet is also relatively overlooked. What is it to think philosophically? How did different forms of thinking - reflection, contemplation, critique and analysis - emerge in different epochs? This collection offers a rich and diverse philosophical exploration of the history of contemplation, from the classical period to the twenty-first century. It covers canonical figures including Plato, Aristotle, Descartes and Kant, as well as debates in less well-known areas such as classical Indian and Islamic thought and the role of speculation in twentieth-century Russian philosophy. Comprising twenty-two chapters by an international team of contributors, the volume is divided into five parts: Flourishing and Thinking from Homer to Hume The Thinking of Thinking from Augustine to Gödel Images and Thinking from Plotinus to Unger Bodies of Thought and Habits of Thinking from Plato to Irigaray The Efficacy of Thinking from Sextus to Bataille. Thought: A Philosophical History is the first comprehensive investigation of the history of philosophical thought and contemplation. As such it is a landmark publication for anyone researching and teaching the history of philosophy, and a valuable resource for those studying the subject in related fields such as literature, religion, sociology and the history of ideas"--